Selective mural cell recruitment of pericytes to networks of assembling endothelial cell-lined tubes - Yrigoin, Ksenia; Davis, George E. (Frontiers in Cell and Developmental Biology, 2024)
Mural cells are critically important for the development, maturation, and maintenance of the blood vasculature. Pericytes are predominantly observed in capillaries and venules, while vascular smooth muscle cells (VSMCs) are found in arterioles, arteries, and veins. In this study, we have investigated functional differences between human pericytes and human coronary artery smooth muscle cells (CASMCs) as a model VSMC type. We compared the ability of these two mural cells to invade three-dimensional (3D) collagen matrices, recruit to developing human endothelial cell (EC)-lined tubes in 3D matrices and induce vascular basement membrane matrix assembly around these tubes. Here, we show that pericytes selectively invade, recruit, and induce basement membrane deposition on EC tubes under defined conditions, while CASMCs fail to respond equivalently. Pericytes dramatically invade 3D collagen matrices in response to the EC-derived factors, platelet-derived growth factor (PDGF)-BB, PDGF-DD, and endothelin-1, while minimal invasion occurs with CASMCs. Furthermore, pericytes recruit to EC tube networks, and induce basement membrane deposition around assembling EC tubes (narrow and elongated tubes) when these cells are co-cultured. In contrast, CASMCs are markedly less able to perform these functions showing minimal recruitment, little to no basement membrane deposition, with wider and shorter tubes. Our new findings suggest that pericytes demonstrate much greater functional ability to invade 3D matrix environments, recruit to EC-lined tubes and induce vascular basement membrane matrix deposition in response to and in conjunction with ECs.